DESIGN AND BUILD ANDALIMAN GERANIOL PARFUME MACHINE (ZANTHOXYLUM ACANTHOPODIUM) - Elysabeth Luisa Pakpahan; Fenny Cloudya Damanik; Zulfran Silaban; Edward Relius Laoli; Rita Juliani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
Andaliman has the Latin name Zanthoxylum acanthopodium and is a family of Rutaceae. Andaliman is a native spice from North Sumatra called the golden spicy from North Sumatra. Andaliman farmers in Parsoburan Village, Toba Samosir said that one of the problems in andaliman production is the number of Andaliman fruits that are still not effective, even most of the Andaliman fruit becomes rotten. The design of Andaliman perfume machine has been carried out which aims to increase the usefulness of Andaliman through the manufacture of andaliman perfume as well as to increase the economic value of Andaliman. The method used is by designing a perfume machine and making an official perfume machine, testing the machine and using a perfume machine. Making perfume machines and testing perfume machines was carried out at the UNIMED Mechanical Engineering Workshop and the implementation of machine use activities was carried out in Parsoburan, Toba Samosir Regency. The results obtained from the andaliman smoothing machine were processed as 2 kg of perfume in a single smoothing process, for the heating stage mixed with 300 mL ethanol and the results of the perfume ± 20 mL which will be mixed with alcohol according to the strong aroma made.